2022
DOI: 10.1111/jmg.12650
|View full text |Cite
|
Sign up to set email alerts
|

Alpine subduction zone metamorphism in the Palaeozoic successions of the Monti Romani (Northern Apennines, Italy)

Abstract: The hinterland of the Cenozoic Northern Apennines fold-and-thrust belt exposes the metamorphic roots of the chain, vestiges of the subduction-related tectono-metamorphic evolution that led to the buildup of the Alpine orogeny in the Mediterranean region. Like in other peri-Mediterranean belts, the tectono-metamorphic evolution of the Paleozoic continental basement in the Apennines is still poorly constrained, hampering the full understanding of their Alpine orogenic evolution. We report the first comprehensive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 145 publications
(313 reference statements)
0
4
0
Order By: Relevance
“…Collectively, these studies have indicated metamorphic conditions of 0.6–1.0 GPa at 420–500°C for the Massa Unit and of 0.4–0.6 GPa at 350–450°C for the Apuane Unit (Figure 15). These thermo‐barometric estimates place the Apuane region apart from the rest of the TMUs of the Northern Apennines, where higher pressures ( P = 1.0–1.8 GPa) have been reported at similar, if not lower, metamorphic temperatures (300–450°C; Theye et al, 1997; Jolivet et al, 1998; Giorgetti et al, 1998; Papeschi et al, 2020; Papeschi, Pontesilli, et al, 2022; Rossetti et al, 1999; Vignaroli et al, 2009; Figure 15).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Collectively, these studies have indicated metamorphic conditions of 0.6–1.0 GPa at 420–500°C for the Massa Unit and of 0.4–0.6 GPa at 350–450°C for the Apuane Unit (Figure 15). These thermo‐barometric estimates place the Apuane region apart from the rest of the TMUs of the Northern Apennines, where higher pressures ( P = 1.0–1.8 GPa) have been reported at similar, if not lower, metamorphic temperatures (300–450°C; Theye et al, 1997; Jolivet et al, 1998; Giorgetti et al, 1998; Papeschi et al, 2020; Papeschi, Pontesilli, et al, 2022; Rossetti et al, 1999; Vignaroli et al, 2009; Figure 15).…”
Section: Discussionmentioning
confidence: 75%
“…Lo Pò and Braga (2014) documented chloritoid with X Mg = 0.16 stabilized at T ~475°C in Fe 2 O 3 ‐bearing bulk‐rock compositions, 75°C lower than the Fe 3+ ‐free case. Similarly, both Lo Pò and Braga (2014) and Papeschi, Pontesilli, et al (2022) reported P–T‐X pseudosections where the predicted appearance of kyanite in the metamorphic assemblage of Al‐rich metapelites appears to be linked exclusively to high‐Fe 2 O 3 contents, highlighting the potential use of chloritoid‐kyanite‐bearing assemblages as tracers of the P–T evolution and the state of oxidation of iron during metamorphism. However, the stability of kyanite or other Al‐silicates as controlled by the ferric iron content, while possible theoretically, has never been documented in low‐grade metamorphic rocks.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These units are capped by foredeep deposits progressively younger toward the external ENE areas of the belt (Boccaletti et al., 1990; Ricci Lucchi, 1986). In the Northern Apennines hinterland, the Tuscan Units (Figure 1) consist of the Tuscan Nappe, characterized by anchizone‐facies passive‐margin sequences (e.g., Baldacci et al., 1967; Ciarapica & Passeri, 1994; Cerrina‐Feroni et al., 1983), and the Tuscan Metamorphic Units, that involve a series of thick‐skinned nappes that registered subduction‐related greenschist‐ to blueschist‐facies metamorphism (Franceschelli et al., 1986; Papeschi et al., 2022; Rossetti et al., 2002; Theye et al., 1997 and references therein). Wedge‐top basins (i.e., Epiligurian Basin; Figure 1) and intermontane basins cover the orogen and show that the belt evolved primarily as an underwater wedge until emersion in the Pliocene (Bonini et al., 2014 and references therein).…”
Section: Geological Backgroundmentioning
confidence: 99%